A Comparative Study "Translatability of English Military Terms into Arabic Language by Translators with Military Backgrounds and Civilian Translators" - Alharahsheh, Abdallah Mohammad Mufadi (Forum for Linguistic Studies, 2024)
This paper examines the translatability of English military terms into Arabic and evaluates the ability of Arab translators to perform such translations. The study compares translations produced by civilian translators and those with military backgrounds, focusing on texts from various military services, including the Land Forces, Presidential Guard, Navy, and Air Force. Using validated texts approved by American military experts and their Arab clients, the research assesses the accuracy, consistency, and contextual appropriateness of translations through both quantitative and qualitative analyses. The findings reveal significant differences in translation quality between the two groups. Translators with military backgrounds demonstrated superior understanding and accuracy in translating military terminology, while civilian translators often struggled with technical aspects, resulting in less precise translations. The study highlights the complexity of military texts and the challenges of finding appropriate Arabic equivalents, noting inconsistencies in civilian translations that could lead to operational misunderstandings. The paper concludes with recommendations to enhance civilian translators' proficiency in military translation. These include establishing specialized training programs, encouraging collaboration between civilian and military translators, and developing comprehensive military dictionaries and glossaries in Arabic. This paper provides valuable insights into the importance of understanding military terms and expressions and highlights the need for targeted efforts to bridge the gap between civilian and military translators.